Between Folk Religion and Material Culture: An Archaeological Study of Arikandam Stones in Chennai - Deepika, S (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2026)
Arikandam, a form of extreme ritual self-sacrifice associated in tradition with acts of devotion, protection, or vow-fulfilment, survives in the archaeological record through sculpted memorial stones that encode ritual action, sacred intent, and community memory. While such practices are primarily preserved in oral narratives and local belief systems, the study foregrounds the stones as durable material culture that bridges intangible ritual traditions and tangible heritage. Field documentation focuses on iconographic features, sculptural conventions, inscriptions (where present), stone typology, weathering patterns, and spatial placement within the sacred landscape in Chennai. These elements are analysed to understand how ritual acts were translated into visual symbols raised weapons, severed heads, offering postures, and divine motifs forming a standardized yet locally inflected memorial vocabulary. Spatial analysis further considers the relationship of these stones to temple complexes. The study situates Arikandam stones within broader South Indian hero-stone traditions while emphasizing their distinct ritual connotations. It argues that these monuments functioned not only as memorials but also as active ritual nodes that sustained collective memory and sacred presence. In the context of urban expansion and temple institutionalization, many such stones have been relocated, absorbed into formal religious settings, or rendered anonymous. Archaeological analysis thus becomes crucial for reconstructing layered histories of devotion, sacrifice, and localized sacred landscapes embedded in stone.
Keywords: Arikandam; Hero Stones; Folk religion; Chennai; Vattaparai Amman; Thoonguthalai; Village Goddess